Co-occuring symptoms in older oncology patients with distinct attentional function profiles. (August 2019) - Utne, Inger; Løyland, Borghild; Grov, Ellen Karine; Paul, Steven; Wong, Melisa L.; Conley, Yvette P.; Cooper, Bruce A.; Levine, Jon D.; Miaskowski, Christine
Abstract: Purpose: Evaluate how subgroups of older adults with distinct attentional function profiles differ on the severity of nine common symptoms and determine demographic and clinical characteristics and symptom severity scores associated with membership in the low and moderate attentional function classes. Methods: Three subgroups of older oncology outpatients were identified using latent profile analysis based on Attentional Function Index (AFI) scores. Symptoms were assessed prior to the second or third cycle of CTX. Logistic regressions evaluated for associations with attentional function class membership. Results: For trait anxiety, state anxiety, depression, sleep disturbance, morning fatigue, and evening fatigue scores, differences among the latent classes followed the same pattern (low > moderate > high). For morning and evening energy, compared to high class, patients in low and moderate classes reported lower scores. For pain, compared to moderate class, patients in low class reported higher scores. In the logistic regression analysis, compared to high class, patients with lower income, higher comorbidity, higher CTX toxicity score, and higher levels of state anxiety, depression, and sleep disturbance were more likely to be in low AFI class. Compared to high class, patients with higher comorbidity and trait anxiety and lower morning energy were more likely to be in moderate AFI class. Conclusions: Consistent with the hypothesis that an increased risk for persistent cognitive decline is likely related to a variety of physical and psychological factors, for six of the nine symptoms, a "dose response" effect was observed with higher symptom severity scores associated with a progressive decline in attentional function. Highlights: Older adults experience numerous concurrent symptoms. Worsening attentional function is associated with a higher symptom burden. A "dose response effect" was observed with higher symptom scores and a progressive decline in attentional function.